2008
DOI: 10.3181/0712-rm-345
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Telomerase Function During Tissue Regeneration

Abstract: Telomerase plays a primary role in the maintenance of telomeres in immortal, germ, and tumor cells in humans but is lacking in most somatic cells and tissues. However, many species, including fish and inbred mice, express telomerase in most cells and tissues. Little is known about the expression of telomerase in aquatic species, although the importance of telomerase for longevity has been suggested. We compared telomerase activity and telomere lengths among a broad range of tissues from aquatic species and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 38 publications
(64 reference statements)
5
61
0
Order By: Relevance
“…In recent years, many fish species have become promising vertebrate models in studies regarding the length of the telomeres and the expression of the telomerase during aging and tissue regeneration [Elmore et al, 2008;Anchelin et al, 2011]. Fluorescence in situ hybridization (FISH) with both conventional and peptide nucleic acid telomeric probes and primed in situ labeling with (TTAGGG) 7 / (CCCTAA) 7 primers made the identification of telomeric DNA sequences in the chromosomes of approximately 80 fish species representing distant taxonomic groups possible [e.g.…”
mentioning
confidence: 99%
“…In recent years, many fish species have become promising vertebrate models in studies regarding the length of the telomeres and the expression of the telomerase during aging and tissue regeneration [Elmore et al, 2008;Anchelin et al, 2011]. Fluorescence in situ hybridization (FISH) with both conventional and peptide nucleic acid telomeric probes and primed in situ labeling with (TTAGGG) 7 / (CCCTAA) 7 primers made the identification of telomeric DNA sequences in the chromosomes of approximately 80 fish species representing distant taxonomic groups possible [e.g.…”
mentioning
confidence: 99%
“…This is in contrast to humans where telomerase activity is absent in most somatic cells but present in embryonic stem cells and tumors (Hiyama and Hiyama, 2007). Although some authors presume that high expression of fish telomerase may be related to the longevity, comparative analysis of telomerase activity in the short-and long-lived fish species showed no positive relationship between telomerase activity and the fish longevity (Elmore et al, 2008). Instead, another hypothesis was suggested: retention of the telomerase in adult fish might be crucial to maintain their regenerative capacity.…”
Section: Distribution Of Telomeric Dna Sequences In Fish 41 Telomeramentioning
confidence: 62%
“…The length of the telomeric DNA in fish studied to date varies from 2 kb to 15 kb (Chew et al, 2002, Elmore et al 2008 and is similar to that observed in normal human cells (Elmore et al, 2008). Furthermore, retention of the telomere length throughout the entire life has been demonstrated in zebrafish, but not in the medaka (Hatekeyama et al, 2008;Lund et al, 2009).…”
Section: Distribution Of Telomeric Dna Sequences In Fish 41 Telomeramentioning
confidence: 66%
See 2 more Smart Citations